(untitled) (Bangladesh Pharmaceutical Journal, 2018)
The present study was designed to investigate the effects of bitter melon (Momordica charantia) in combination with a standard oral hypoglycemic agent metformin on alloxan induced diabetic rats (AIDRs). Both the plant extract and the drug, individually and in combination, were subjected in vivo for two weeks (short term) and four weeks (long term) treatment protocol to determine blood glucose level, lipid profile and liver glycogen level using Swiss Albino rats. In short term treatment protocol, bitter melon extract (BME) at a dose of 75, 150 and 300 mg/ kg body weight (bw) were administered in AIDRs by using oral gavages once daily and dose-dependent antihyperglycemic and antidyslipidemic effects were investigated. This short term study revealed that the most effective dose of BME was found as 300 mg/kg bw among the three doses. In long term treatment protocol, AIDRs in different groups received fixed dose monotherapy of BME (300 mg/kg bw) and metformin (15 mg/kg bw) and fixed dose BME (150 mg/kg bw) and metformin (7.5 mg/kg bw) combination therapy. The study showed that combination therapy significantly decreased the blood glucose level from 18.42 ± 0.95 to 6.80 ± 0.39 mmol/l in comparison to the control group after daily treatment for four weeks. In case of antidyslipidemic effect, combination therapy reduced total cholesterol (34.25%), triglycerides (11.92%) and LDL-cholesterol (57.73%) levels and increased HDL-cholesterol level (55.48%) in comparison with their respective control groups. Metformin, BME and their combination preserved the liver glycogen level by 35.21%, 22.54% and 49.01%, respectively in comparison to diabetic control group. These changes were significantly better than those of BME and metformin monotherapy. The results suggested that treatment with combination therapy was more effective than mono-therapy for preventing diabetes as bitter melon extract potentiates the effects of metformin on long term alloxan-induced diabetic rats. Bangladesh Pharmaceutical Journal 21(2): 109-117, 2018